2015
DOI: 10.1002/mas.21471
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of carbohydrates and glycoconjugates by matrix‐assisted laser desorption/ionization mass spectrometry: An update for 2011–2012

Abstract: This review is the seventh update of the original article published in 1999 on the application of MALDI mass spectrometry to the analysis of carbohydrates and glycoconjugates and brings coverage of the literature to the end of 2012. General aspects such as theory of the MALDI process, matrices, derivatization, MALDI imaging, and fragmentation are covered in the first part of the review and applications to various structural types constitute the remainder. The main groups of compound are oligo- and poly-sacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 1,685 publications
(685 reference statements)
0
29
0
Order By: Relevance
“…According to previous studies, direct analysis of native sialylated glycans is difficult, as the negative charge of sialic acid reduces the ionization efficiency in positive-ion mode and the non-derivatized sialic acid residues are often lost due to in- and post source decay [19, 40]. Although negative-ion mode MS is proposed as an alternative option for MALDI analysis of native acidic glycans, it has been demonstrated that the sensitivity of sialylated glycans is at least 10 times less than neutral glycans when using DHB as a matrix [41].…”
Section: Resultsmentioning
confidence: 99%
“…According to previous studies, direct analysis of native sialylated glycans is difficult, as the negative charge of sialic acid reduces the ionization efficiency in positive-ion mode and the non-derivatized sialic acid residues are often lost due to in- and post source decay [19, 40]. Although negative-ion mode MS is proposed as an alternative option for MALDI analysis of native acidic glycans, it has been demonstrated that the sensitivity of sialylated glycans is at least 10 times less than neutral glycans when using DHB as a matrix [41].…”
Section: Resultsmentioning
confidence: 99%
“…Various solid and liquid matrices have been reported for enhancing the ion yield of glycans. [9][10][11][12][13][14][15] Another way to improve ionization eciency is to perform derivatization (i.e., labeling). e chemical labeling of the reducing end of glycans was originally developed for HPLC analysis with UV or uorescent detectors.…”
Section: Labeling Of Glycansmentioning
confidence: 99%
“…us, MALDI-MS enjoys widespread use in a variety of applications for the analysis of glycans and glycopeptides. [9][10][11][12][13][14][15] However, the mass spectrometric analysis of glycosylation still remains a challenging task due to the low ionization e ciency, labile nature and complicated branched structures involving various linkage isomers. In general, released glycans show lower ionization e ciency than other biopolymers, such as peptides.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of native N-glycans revealed that the O -acetylation pattern was correlated with long-term handling stress, which was most likely to be a product of immune reaction. With the permethylation process, MALDI-MS is the desired technique for profiling glycans28293031. Methylation of all hydroxyl groups of glycans can significantly increase detection sensitivity because the derivatives are considerably more hydrophobic and stable than native glycans.…”
mentioning
confidence: 99%